A benchmarking method to measure dietary absorption efficiency of chemicals by fish. (1st October 2013) - Xiao, Ruiyang; Adolfsson‐Erici, Margaretha; Åkerman, Gun; McLachlan, Michael S.; MacLeod, Matthew
Abstract Understanding the dietary absorption efficiency of chemicals in the gastrointestinal tract of fish is important from both a scientific and a regulatory point of view. However, reported fish absorption efficiencies for well‐studied chemicals are highly variable. In the present study, the authors developed and exploited an internal chemical benchmarking method that has the potential to reduce uncertainty and variability and, thus, to improve the precision of measurements of fish absorption efficiency. The authors applied the benchmarking method to measure the gross absorption efficiency for 15 chemicals with a wide range of physicochemical properties and structures. They selected 2, 2′, 5, 6′‐tetrachlorobiphenyl (PCB53) and decabromodiphenyl ethane as absorbable and nonabsorbable benchmarks, respectively. Quantities of chemicals determined in fish were benchmarked to the fraction of PCB53 recovered in fish, and quantities of chemicals determined in feces were benchmarked to the fraction of decabromodiphenyl ethane recovered in feces. The performance of the benchmarking procedure was evaluated based on the recovery of the test chemicals and precision of absorption efficiency from repeated tests. Benchmarking did not improve the precision of the measurements; after benchmarking, however, the median recovery for 15 chemicals was 106%, and variability of recoveries was reduced compared with before benchmarking, suggesting that benchmarking could account for incomplete extraction of chemical in fish and incomplete collection of feces from different tests. Environ Toxicol Chem 2013;32:2695–2700. © 2013 SETAC